The Abundance and Sources of Ice Nucleating Particles Within Alaskan Ice Fog - Lill, Emily; Costa, Emily J.; Barry, Kevin; Mirrielees, Jessica A.; Mashkevich, Monica; Wu, Judy; Holen, Andrew L.; Cesler‐Maloney, Meeta; DeMott, Paul J.; Perkins, Russell; Hill, Thomas; Sullivan, Amy; et al. (Journal of geophysical research. Atmospheres, 2024)
The Alaskan Layered Pollution and Chemical Analysis (ALPACA) field campaign included deployment of a suite of atmospheric measurements in January–February 2022 with the goal of better understanding atmospheric processes and pollution under cold and dark conditions in Fairbanks, Alaska. We report on measurements of particle composition, particle size, ice nucleating particle (INP) composition, and INP size during an ice fog period (29 January–3 February). During this period, coarse particulate matter (PM10) concentrations increased by 150% in association with a decrease in air temperature, a stronger temperature inversion, and relatively stagnant conditions. Results also show a 18%–78% decrease in INPs during the ice fog period, indicating that particles had activated into the ice fog via nucleation. Peroxide and heat treatments performed on INPs indicated that, on average, the largest contributions to the INP population were heat‐labile (potentially biological, 63%), organic (31%), then inorganic (likely dust, 6%). Measurements of levoglucosan and bulk and single‐particle composition corroborate the presence of dust and aerosols from combustion sources. Heat‐labile and organic INPs decreased during the peak period of the ice fog, indicating those were preferentially activated, while inorganic INPs increased, suggesting they remained as interstitial INPs. In general, INP concentrations were unexpectedly high in Fairbanks compared to other locations in the Arctic during winter. The fact that these INPs likely facilitated ice fog formation in Fairbanks has implications for other high latitude locations subject to the hazards associated with ice fog. Plain Language Summary The Alaskan Layered Pollution and Chemical Analysis field campaign occurred January–February 2022 with the goal of better understanding the atmosphere and atmospheric pollution during the winter in Fairbanks, Alaska. We studied a rare subset of atmospheric particles called ice nucleating particles which facilitate the formation of ice fog by allowing water to freeze at temperatures above −38°C. During our study, there was an ice fog event that coincided with a pollution event. During this event, there was a significant increase in coarse particulate matter associated with a decrease in temperature and calm winds. Ice nucleating particle concentration in the air decreased during the ice fog event indicating that the INPs had activated into the ice fog and were not able to be captured. We determined that most INPs were heat‐labile (potentially biological), followed by organic. Very few INPs were inorganic. Inorganic INPs increased during the ice fog period while heat‐labile and organic INPs decreased indicating that they were being selectively activated into the fog. Overall, INP concentrations in Fairbanks were quite high compared to other Arctic locations and carries implications for ice fog formation in other high‐latitude locations. Key Points Fairbanks had higher wintertime ice nucleating particle (INP) concentrations than other high‐latitude locations INP concentrations in Fairbanks decreased during the ice fog period, indicating that INPs were activated into the fog INP composition in Fairbanks was dominated by heat‐labile INPs